Screening of rhizobacterial isolates against soft rot disease of ginger (Zingiber officinale Rosc.) - Anandaraj, S J Eapen, R S Bhai, V K Kishore, A Kumar, M (Journal of Spices and Aromatic Crops, 2005)
Twenty rhizobacterial cultures including Pseudomonas fluorescens, Enterobacter agglomerans and Bacillus sp. were tested under in vitro and in vivo conditions to evaluate their efficacy in inhibiting Pythium myriotylum and reducing the incidence of soft rot disease in ginger (Zingiber officinale). Under in vitro conditions, 19 of the tested rhizobacterial cultures significantly inhibited P. myriotylum. Evaluation of these cultures under in vivo conditions indicated that seven of the isolates were effective in suppressing the pathogen. Five of the isolates when inoculated along with Glomus sp. (vesicular arbuscular mycorrhizae) also enhanced root development without disease incidence.